Apical transportation of manual NiTi instruments and a hybrid technique in severely curved simulated canals - Gonçalves, Aurenaila Nascimento; Da Frota, Matheus Franco; Sponchiado Júnior, Emilio Carlos; De Carvalho, Fredson Marcio Acris; Da Fonseca Roberti Garcia, Lucas [UNESP]; Marques, André Augusto Franco (Wolters Kluwer, 2015)
Aim: To evaluate the apical transportation induced by two instrumentation techniques in severely curved simulated canals. Materials and Methods: Forty simulated canals were divided into two groups (n = 20), according to the following instrumentation techniques: ProTaper Universal Manual System and a hybrid technique. The simulated canals in the ProTaper group were prepared following the technique recommended by the manufacturer: SX files in the cervical third of the root canal and S1, S2, and F1 files up to the working length. In the hybrid group, preparation was performed with K-files sizes 15, 20, and 25 to the working length, followed by cervical preparation with Gates Glidden burs 1, 2, and 3. Apical finishing was performed with the ProTaper manual files S2 and F1. To analyze apical transportation, the simulated canals were photographed before and after preparation at ×8. The images of the root canals pre- and post-instrumentation were superimposed to measure the distance between the inner and outer walls along the first 3 mm of the apical third. Results: The hybrid group presented the highest apical transportation values; however, with no statistically significant difference in comparison with the ProTaper group (P > 0.05). Conclusions: Both techniques induced similar apical transportation in the original path of the simulated root canals.
Keywords: Apical transportation; endodontics; root canal therapy